2015
DOI: 10.1017/s1041610215002094
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized controlled trial of a self-management group intervention for people with early-stage dementia (The SMART study)

Abstract: Background: Self-management equips people to manage the symptoms and lifestyle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 21 publications
3
78
0
Order By: Relevance
“…Thus, there is On the other hand, there is a growing interest for self-management in dementia, and the views of people with dementia being unable to learn new skills are being challenged (Mountain, 2006). The small number of studies being conducted in the area has shown promising results for participant's general wellbeing and sense of self-efficacy (see for example Quinn et al 2016b;Sprange et al 2015;Hickman, Wiersma & Harvey, 2015;Laakkonen, Kautiainen, Hölttä, Saivikko, Tilvis & Strandberg et al 2016). …”
Section: Meaningful Activities and Relationshipsmentioning
confidence: 99%
“…Thus, there is On the other hand, there is a growing interest for self-management in dementia, and the views of people with dementia being unable to learn new skills are being challenged (Mountain, 2006). The small number of studies being conducted in the area has shown promising results for participant's general wellbeing and sense of self-efficacy (see for example Quinn et al 2016b;Sprange et al 2015;Hickman, Wiersma & Harvey, 2015;Laakkonen, Kautiainen, Hölttä, Saivikko, Tilvis & Strandberg et al 2016). …”
Section: Meaningful Activities and Relationshipsmentioning
confidence: 99%
“…We found 10 studies 37,59,62,106,109,110,115,121,132,136 looking at SM interventions for people living with dementia or cognitive impairment, only one of which included people with dementia and diabetes. 59 This controlled study evaluated the impact of personalised education sessions on people with diabetes and cognitive impairment.…”
Section: Stigma and Barriers To Care For People Living With Dementiamentioning
confidence: 99%
“…147 This literature does, however, provide valuable insights into what needs to be in place to support independence and appropriate outcomes in people living with dementia, much of which might form the basis for programmes for people with dementia and diabetes. Potentially important components of such programmes include the need to focus on the abilities and strengths of people with dementia rather than their disabilities, 109,110 on emotions rather than problems, 109 on building confidence 62,121 and on respecting participant autonomy and enhancing empowerment. 106 Social interaction may also be important.…”
Section: Stigma and Barriers To Care For People Living With Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…The PRIDE study comprises five interrelated strands investigating early/mild dementia. The first two strands involved an epidemiological investigation into the risk and protective factors associated with dementia in two large longitudinal databases of older adults in England and Brazil (11) and a qualitative exploration of social discourses of dementia focusing on the themes of memory and independence, involving interviews and observations with adults ranging from those with no memory problems to those two years post diagnosis (12). These two studies contributed to the development of the PRIDE intervention, along with existing literature, which was then tested to inform present feasibility randomised controlled trial.…”
Section: Introductionmentioning
confidence: 99%